Climate-driven hydrological sensitivity in Estonian catchments: a northern temperate perspective - Oliver Koit; Joonas Pärn; Marlen Hunt; Siim Tarros; Elve Lode; Pamela Abreldaal (Estonian Journal of Earth Sciences)
The escalating impacts of global climate change significantly affect regional hydrological systems, particularly in northern areas such as Estonia. This study investigates the hydrological sensitivity of Estonian catchments to climatic variability, focusing on the interplay between surface water and groundwater. Using data from 42 river catchments, it employs various statistical methods in hydrology, emphasizing the autocorrelation function, cross-correlation function, baseflow index, and flow duration curve. The analysis spans the years 2012â2022, integrating hydrological, spatial, and water quality parameters. The research identifies four distinct hydrological behavior clusters: plateau, sandstone upland, carbonate upland, and lowland. Key findings include diverse catchment sensitivities to groundwater recharge, the role of baseflow in streamflow stabilization, the memory effect in catchment responses, and insights from the flow duration curve on flow variability and extremes. The LightGBM model, predicting focus parameters, highlights the critical influence of air temperature and snowpack on streamflow characteristics. This study underscores the diverse hydrological sensitivities of Estonian catchments to hydroclimatic changes, emphasizing the importance of considering catchment-specific characteristics in water resource management and policy-making. Contributing to the broader understanding of hydrological processes, it provides valuable insights for future research and environmental planning in the face of climate variability and change.